2006
DOI: 10.1093/hmg/ddl108
|View full text |Cite
|
Sign up to set email alerts
|

Neurofibroma-associated growth factors activate a distinct signaling network to alter the function of neurofibromin-deficient endothelial cells

Abstract: Genetic inactivation of tumor suppressor genes initiates human cancers. However, interaction of accessory cells with the tumor-initiating cell within the microenvironment is often required for tumor progression. This paradigm is relevant to understanding neurofibroma development in neurofibromatosis type I patients. Somatic inactivation of the Nf1 tumor suppressor gene, which encodes neurofibromin, is necessary but not sufficient to initiate neurofibroma development. In contrast, neurofibromas occur with high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 50 publications
3
46
0
1
Order By: Relevance
“…Therefore, excessive infiltration of Nf1 +/-inflammatory cells into the neointima is an important observation, since chronic inflammation may promote EC senescence and increased VSMC proliferation (11,12) in NF1 patients, resulting in vascular lesion formation. Neurofibromin has clearly been established as a critical regulator of EC, VSMC, and BM cell function in vitro and in vivo in response to multiple growth factors implicated in vessel wall homeostasis and neointima formation (13)(14)(15)(16). However, despite these observations, it remains unclear which cell lineage(s) are the major contributor to neointima formation in Nf1 +/-mice, and this determination is essen-tial to understand the pathophysiology of NF1 vascular disease and potential therapeutic interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, excessive infiltration of Nf1 +/-inflammatory cells into the neointima is an important observation, since chronic inflammation may promote EC senescence and increased VSMC proliferation (11,12) in NF1 patients, resulting in vascular lesion formation. Neurofibromin has clearly been established as a critical regulator of EC, VSMC, and BM cell function in vitro and in vivo in response to multiple growth factors implicated in vessel wall homeostasis and neointima formation (13)(14)(15)(16). However, despite these observations, it remains unclear which cell lineage(s) are the major contributor to neointima formation in Nf1 +/-mice, and this determination is essen-tial to understand the pathophysiology of NF1 vascular disease and potential therapeutic interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, Krox20cre mice crossed into mice with mice carrying two distinct W mutations, a mutation which compromises c-kit receptor tyrosine kinase activity and inhibits mast cell production and bioactivity [36]. [20,[38][39][40]. Moreover, SCF-stimulated Nf1 +/− mast cells, as compared to WT mast cells, proliferate more quickly, demonstrate enhanced survival, and secrete greater concentrations of inflammatory cytokines [38,[41][42][43].…”
mentioning
confidence: 99%
“…Wu et al 163 have recently demonstrated that NF1 +/-endothelial cells undergo increased neovascularization when exposed to hypoxia and the angiogenic factor bFGF, as compared to wildtype littermates in a mouse model. Separately, Munchoff et al 107 have provided mouse in vitro and in vivo data corroborating these findings and implicating a Ras-dependent pathway, verified in tissue from a patient with NF1, in the process of neoangiogenesis. A wide variety of additional stimulatory autocrine and paracrine growth factors have been implicated as contributors to the tumor-promoting environment.…”
Section: Contributions Of the Local Microenvironment A Large Quantitmentioning
confidence: 79%